2019
DOI: 10.1001/jamaoto.2018.4515
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Cutaneous Squamous Cell Carcinoma in the Head and Neck Region With Regional Lymph Node Metastasis

Abstract: IMPORTANCE There is a need to summarize the available evidence and provide quantitative data of the most important prognostic factors for patients with metastatic cutaneous squamous cell carcinoma of the head and neck region with regional lymph node metastasis (McSCCHN). OBJECTIVE To undertake a PRISMA-compliant systematic review and meta-analysis of all published studies on the risk factors for overall survival (OS), locoregional control (LRC), locoregional recurrence (LRR), and disease-specific survival (DSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 63 publications
(86 reference statements)
4
42
2
Order By: Relevance
“…For patients with cSCC in the head and neck region with regional metastases, a recent meta-analysis performed by Sahovaler et al (20 observational studies and 1 randomised phase III study [62] improved disease-specific survival (DSS) and OS of adjuvant RT. In this meta-analysis, PNI was not associated with poorer OS, while extracapsular extension was [63].…”
Section: Postoperative Adjuvant Rtmentioning
confidence: 54%
See 2 more Smart Citations
“…For patients with cSCC in the head and neck region with regional metastases, a recent meta-analysis performed by Sahovaler et al (20 observational studies and 1 randomised phase III study [62] improved disease-specific survival (DSS) and OS of adjuvant RT. In this meta-analysis, PNI was not associated with poorer OS, while extracapsular extension was [63].…”
Section: Postoperative Adjuvant Rtmentioning
confidence: 54%
“…The risk of bias is significant in these articles, being based mostly on a retrospective design, also patients with worse prognosis and comorbidities may not have received adjuvant RT [63], and the possibility that patients who received adjuvant RT may not have had clear surgical margins and may have had other poor prognostic factors [15]. The great variation in results, however, suggests that a subset of patients may derive benefit from adjuvant RT.…”
Section: Postoperative Adjuvant Rtmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymph node metastases occurs in a small subset of patients with cutaneous NMSC, and recommendations for management are based largely on retrospective data at single-center institutions. [20][21][22] Currently, there is still much heterogeneity regarding the utility of sentinel lymph node biopsy (SLNB) or regional lymphadenectomy in cutaneous SCC. 9 One study showed an 18.4% positive rate of locoregional disease with patients who underwent SLNB, but there was no difference in disease-specific survival compared to patients who did not have an SLNB.…”
Section: Discussionmentioning
confidence: 99%
“…4,6,7 There have been attempts to determine the point at which the benefit of electively treating clinically negative neck lymph nodes exceed treatment-related morbidity. [8][9][10][11][12][13][14] Unfortunately, however, the risk factors known to increase the likelihood for regional neck metastasis, especially tumor diameter of 2 cm or more and depth of invasion, are not sufficiently predictive to help decide whether a potentially morbid surgery encompassing parotidectomy and neck dissection is needed. [1][2][3][4] Besides the typical pathways for metastatic spread, the parotid intraglandular lymph nodes (IGLNs) represent the first metastatic relay for cSCCHN of the face and scalp.…”
Section: Introductionmentioning
confidence: 99%